2012
DOI: 10.4103/0970-0358.105956
|View full text |Cite
|
Sign up to set email alerts
|

Thoracodorsal artery perforator fasciocutaneous flap: A versatile alternative for coverage of various soft tissue defects

Abstract: Objective:The thoracodorsal artery perforator (TDAP) flap has contributed to the efficient reconstruction of tissue defects that require a large amount of cutaneous tissue. The optimal reconstruction method should provide thin, and well-vascularized tissue with minimal donor-site morbidity. The indications for the use of this particular flap with other flaps are discussed in this article.Materials and Methods:Thirteen patients underwent soft tissue reconstruction using TDAP flaps between 2009 and 2011. Of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
1
24
2
Order By: Relevance
“…The donor site was closed primarily in 16 cases (80%). Although there are some studies denoting the ability to primarily close the donor site of the TDAP flap up to 12cm width [14], we found that the maximum width that can be closed primarily is 10cm and this is attributed to the presence of all intact LD muscle in the field.…”
Section: Discussioncontrasting
confidence: 59%
“…The donor site was closed primarily in 16 cases (80%). Although there are some studies denoting the ability to primarily close the donor site of the TDAP flap up to 12cm width [14], we found that the maximum width that can be closed primarily is 10cm and this is attributed to the presence of all intact LD muscle in the field.…”
Section: Discussioncontrasting
confidence: 59%
“…The pedicled thoracodorsal artery perforator flap (TAP flap) has been demonstrated to be a versatile flap, suitable for several reconstructive purposes. [1][2][3][4][5] Its use and benefits in breast reconstruction has been established previously. [6][7][8][9][10][11][12][13][14][15][16][17] Several publications describe the TAP-flap combined with an implant for total breast reconstruction, suggesting it as an alternative to the conventional musculocutaneous latissimus dorsi flap (LD flap).…”
Section: Conclusion Introductionmentioning
confidence: 99%
“…The TDAP free flap can provide a large skin paddle and long pedicle, similar to the ALT free flap. 12 However, in the present case, a position change during operation would be needed using the TDAP free flap. The TDAP free flap was planned as an option for covering when the reverse ALT flap was not possible.…”
Section: Discussionmentioning
confidence: 78%